The Neuromuscular Junction in Health and Disease: Molecular Mechanisms Governing Synaptic Formation and Homeostasis - Rodríguez Cruz, Pedro M.; Cossins, Judith; Beeson, David; Vincent, Angela (Frontiers in Molecular Neuroscience, 2020)
The neuromuscular junction (NMJ) is a highly specialised synapse between a motor neuron nerve terminal and its muscle fibre that are responsible for converting electrical impulses generated by the motor neuron into electrical activity in the muscle fibres. On arrival of the motor nerve action potential, calcium enters the presynaptic terminal, which leads to the release of the neurotransmitter acetylcholine (ACh). ACh crosses the synaptic gap and binds to ACh receptors (AChRs) tightly clustered on the surface of the muscle fibre; this leads to the endplate potential which initiates the muscle action potential that results in muscle contraction. This is a simplified version of the events in neuromuscular transmission that take place within millisecs, and are dependent on a tiny but highly structured NMJ. Much of this review is devoted to describing in more detail the development, maturation, maintenance and regeneration of the NMJ, but first we describe briefly the most important molecules involved and the conditions that affect their numbers and function. Most important clinically worldwide, are myasthenia gravis (MG), the Lambert-Eaton myasthenic syndrome (LEMS) and congenital myasthenic syndromes (CMS), each of which causes specific molecular defects. In addition, we mention the neurotoxins from bacteria, snakes and many other species that interfere with neuromuscular transmission and cause potentially fatal diseases, but have also provided useful probes for investigating neuromuscular transmission. There are also changes in NMJ structure and function in motor neuron disease, spinal muscle atrophy and sarcopenia that are likely to be secondary but might provide treatment targets. The NMJ is one of the best studied and most disease-prone synapses in the nervous system and it is amenable to in vivo and ex vivo investigation and to systemic therapies that can help restore normal function.